PENGARUH WAKTU PEMBERIAN MIKORIZA PADA BEBERAPA VARIETAS TERHADAP PERTUMBUHAN DAN HASIL TANAMAN MENTIMUN (CUCUMIS SATIVUS L.) - Albert Boly Lewar; Putu Pandawani; Cokorda Javandira (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2019)
Increased crop production is a major part in the cultivation of plants is no exception in cucumber (Cucumis sativus L.). Cucumber is one type of vegetables from the family cucurbitacea (labu-Labuan) which is very popular among the people of Indonesia. Cucumber cultivation extends throughout the world, both hot climates (tropical) and temperate (sub-tropical). Research on the effect of time of mycorrhizal administration on several varieties on the growth and yield of cucumis sativus l. Production has been done in Bona Village of Giannyar Bali Regency from February to May 2017. This study aims to know when the exact time of giving mycorrhiza to the land and appropriate varieties for planting.This research uses Factorial RAK calculation. With 3 treatment time of application, 3 treatment of varieties, combination of treatment time of application and varieties. Delivery time 1 week before planting is the right time to administer mycorrhizae to the planting area, and Manggala is the best variety. Based on RAK test result, the best combination treatment was MS 1 SBT with total fruit weight (9,488) and then decreased successively in treatment of RO I SBT (9,182) and MG I SBT was 8,983. The lowest yield on the combination treatment of varieties and the time of administration on the observation parameter was the MG TM treatment with the total weight (5,483).